The State of Juvenile Delinquency in India: Present & Future By- Kshipra Mahadik - Mahadik, Kshipra; Nagarathna, BV (Trinity Law Review, 2025)
Juvenile delinquents are not inherently criminals but often victims of parental or societal neglect. The juvenile justice system, distinct from the adult criminal justice framework, emphasizes rehabilitation over punishment, aiming to reintegrate young offenders into society. Juvenile Justice Boards prosecute cases with less stringent procedures, focusing on education, counselling, and family support. This article examines how judicial precedents influence the re-integration process of juveniles and explores whether current measures are sufficient to ensure their return as responsible citizens. It also evaluates the need for further reforms in light of socio-economic changes and technological advancements that continue to shape juvenile behavior and justice delivery.